Local Original Revenue Receipts Before and After Electronification Local Government Transactions - Muhtarom Muhatarom (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
Purpose – This study aims to determine the difference in local revenue receipts before and after the Electronification of Local Government Transactions.Methodology – This study used a quantitative approach. The data used is secondary in reports on regional original income realization (2019-2022). The population used is the original income data from the Regency / City in Banten Province. The sample used in this study is data on the original revenue receipts of districts/cities in Banten Province from 2019 to 2022, using purposive sampling techniques. The data analysis techniques used are descriptive statistical analysis and metric difference tests, namely paired sample t-test difference tests.Findings – There is no difference in Local Original Revenue receipts before and after implementing the District/City Government Transaction policy in Banten Province. Although there is no significant difference, there needs to be an in-depth evaluation of the implementation of the policy.Originality / Novelty – Although electronification focuses on Banten Province and provides a specific context that has not been explored much in previous literature, it combines PAD analysis before and after the implementation of electronification policies to provide a comprehensive picture of the impact of these policies.Implications – Further evaluation of the implementation of this policy needs to be done. Investment is needed in training and empowering Human Resources (HR) to support technology effectiveness while maintaining public trust in electronic transactions and preventing unethical practices.